Aromatase Promoter I.f is Regulated by Estrogen Receptor Alpha (ESR1) in Mouse Hypothalamic Neuronal Cell Lines(1) - Yilmaz, M. Bertan (Biol Reprod, 2009)
Aromatase (CYP19A1) catalyzes the conversion of C(19) steroids to estrogens. Aromatase and its product estradiol (E(2)) are crucial for the sexually dimorphic development of the fetal brain and the regulation of gonadotropin secretion and sexual interest in adults. The regulation of aromatase expression in the brain is not well understood. The aromatase (Cyp19a1) gene is selectively expressed in distinct neurons of the hypothalamus through a distal brain-specific promoter I.f located ∼36 kb upstream of the coding region. Here, we investigated a short feedback effect of E(2) on aromatase mRNA expression and enzyme activity using estrogen receptor alpha (ESR1; also known as ERalpha)-positive or ESR1-negative mouse embryonic hypothalamic neuronal cell lines that express aromatase via promoter I.f. Estradiol regulated aromatase mRNA expression and enzyme activity in a time- and dose-dependent manner, whereas an E(2) antagonist reversed these effects. The nucleotide −200/−1 region of promoter I.f conferred E(2) responsiveness. Two activator protein 1 (AP-1) elements in this region were essential for induction of promoter activity by E(2). ESR1 and JUN (c-Jun) bound to these AP-1 motifs in intact cells and under cell-free conditions. The addition of an ESR1 mutant that interacts with JUN but not directly with DNA enhanced E(2)-dependent promoter I.f activity. Independently, we demonstrated an interaction between ESR1 and JUN in hypothalamic cells. Knockdown of ESR1 abolished E(2)-induced aromatase mRNA and enzyme activity. Taken together, E(2) regulates Cyp19a1 expression via promoter I.f by enhanced binding of an ESR1/JUN complex to distinct AP-1 motifs in hypothalamic cells. We speculate that this mechanism may, in part, regulate gonadotropin secretion and sexual activity.